A benchmarking analysis of the economic development in Romania and Czech Republic - Cristinel CONSTANTIN; Adrian MICU (Risk in Contemporary Economy, 2018)
A higher economic development is a goal of every country which is interested in assuring a higher living standard to its citizens. Nevertheless the reality reveals big differences between countries even inside the same economic community. Our research starts from such a problem which finds Romania one of the less developed countries in European Union. Aiming at a benchmarking analysis between Romania and Czech Republic we found that the economic development could be related to public policies that should be oriented towards a better spending of money on economic and social purposes.